HUBUNGAN KAPABILITAS PEMASARAN DAN OPERASI TERHADAP KINERJA PERUSAHAAN - Dompas, Saartje Laoh (JBE (Journal of Business and Economics); Volume 7 No.2, 2008 JBE UNKLAB, 2008)
Market capability has been consider as co variable to support corporation market to a chief corporate out comes how ever corporate size level on the other hand has also been in line to maintain corporate out comes. While in differences corporate performance has shown as a potential moderator to the same corporate out comes. Bivariate correlations were used to test the interrelations of the above variables. Since market capability significantly effects comparative advantage attainment continually, managers were recommended to design a strategy which enhances revenue growth and shareholder’s value.